Acute Effects of Different Types of Resistance Training on Cardiac Autonomic Modulation in COPD - Vanderlei, Franciele M. [UNESP]; Zandonadi, Fernando [UNESP]; Lima, Fabiano Francisco de [UNESP]; Silva, Bruna S. A. [UNESP]; Freire, Ana Paula C. F. [UNESP]; Ramos, Dionei [UNESP]; Ramos, Ercy Mara C. [UNESP] (Daedalus Enterprises Inc, 2018)
BACKGROUND: An exercise modality that has been gaining significant importance in the rehabilitation of subjects with COPD is resistance training. When considering that patients with COPD present alterations in autonomic cardiac modulation caused by the disease itself, it is necessary to investigate the behavior of the autonomic nervous system in relation to this type of exercise. Thus, the objective of this study was to compare the acute effects of resistance training with elastic tubes, elastic bands, and conventional weightlifitng on the behavior of cardiac autonomic modulation in post-exercise recovery in subjects with COPD. METHODS: Thirty-four subjects with COPD performed an single session of resistance training divided according to the therapeutic resource used: elastic tubes (n = 10), elastic bands in = 11), and conventional bodybuilding (n = 13). For analysis of cardiac autonomic modulation, the heart rate was obtained beat to beat at rest and immediately after the end of the session for 60 min in a seated position. Heart rate variability indices were obtained in the time and frequency domains. RESULTS: The 3 therapeutic resource types used in the single session of resistance training promoted changes in heart rate variability linear indices in the time and frequency domains; however, post-exercise recovery time was similar for all protocols performed. CONCLUSIONS: After single resistance training the elastic tubes group presented a minimum alteration in the post-exercise recovery of cardiac autonomic modulation in the subjects with COPD; however, at 5 min after exercising, the subjects with COPD had already recovered. Therefore, if the purpose of the training is to restore autonomic cardiac modulation, the use of elastic tubes is suggested, when considering their low cost and versatility.
Keywords: heart rate variability; autonomic nervous system; physical exercise; resistance training; COPD; rehabilitation elastic tubes